Isolation and Characterisation of Bifidobacterium Spp. from Infant Stools - Mustafa, Shuhaimi (1999)
Infant faecal materials from different feeding regimes (breast fed, breast fed supplemented with mixed diet and bottle fed) were analysed for their distribution of microbes and isolation of bifidobacteria. The predominant bacteria in breast-fed infants after 23 weeks were streptococci and bifidobacteria. The predominant bacteria in breast-fed supplemented with mixed diet after 24 weeks were clostridia, streptococci and bifidobacteria. In the bottle fed infant faeces, bifidobacteria was present in small numbers whereas lactobacilli were one of the most predominant bacteria. 18 isolates of Bifidobacterium in/antis and 10 isolates of Bifidobacterium breve were isolated and tested for their antibacterial activity, survival in low pH conditions, and adhesion to human colon carcinoma cell lines . Three isolates (B. in/antisC040225, B. breve F0526100 and B. breve G012048) exhibited good antibacterial activity. These isolates inhibit the growth of Salmonella enteritidis, Vibrio cholera, Escherichia coli, Bacillus cereus, Pseudomonas aerugmosa and Listeria monocytogenes. The survival rate of bifidobacteria in low pH condition was variable among isolates. All the isolates tested showed good survival in control solution (pH 6.5). None of the isolates tested was able to survive at pH 1.0 after 1 hour incubation. However, at pH 2.0, five isolates (B. infantis D042022, B. infantis F042466, B. infantis F0526100 and B. infantis G001204) survived after 1h incubation but not after 2h incubation at this pH. Four strains (B. infantis D04 2022, B. infantis F0606117, B. infantis F041134 and B. infantis Z040845) possessed good survival at pH 3.0 where viable cells could still be detected after 3 hours incubation. One of the most important criteria of probiotic micro-organism is the ability to adhere and colonise to human intestinal epithelial cells in order to prevent them from being flushed out by the peristaltic movement in the gastrointestinal tract. B. infantis G001204 was found to adhere well to HT29 cell lines in culture. Not all the bifidobacteria isolates tested possessed all the characteristics of probiotic.